Sovereignty and Decentralization – two competing perspectives on the crisis of the French monarchy in the 16th century - Maciej Wilmanowicz (Czasopismo Prawno-Historyczne)
The purpose of this paper is to analyze two significant treatises concerning the constitutional structure of the 16th century French monarchy, namely Jean Bodin’s Les Six livres de la République and Vindiciae, contra tyrannos written under the pseudonym of Brutus. The texts were answers to an ongoing institutional crisis of the monarchy, especially in light of the strictly connected issues of decentralization and the weakness of the royal administrative apparatus. The paper portrays how the tension between the royal administration and the complicated structure of the local networks of power not only rendered it impossible for both Bodin and Brutus not to take a stance on the matter but also how it influenced the shape of their theories. An analysis of how Brutus and Bodin tried to incorporate the complex institutional realities of the French kingdom into their own theories sheds some light on the authors’ attitude towards the functioning of the local centres of power, their theoretical disabling or using them on purpose; it also points to how much the actual decentralization of the state influenced the shape of the theories of both authors.